THE EFFECTIVENESS OF USING BLOG IN TEACHING WRITING SKILL: A Pre Experimental Research to The Sixth Semester Study Of English Education Program of a Private University in Pontianak - Almu Bakrin; Aunurrahman; Ageung Darajat (Program Studi Pendidikan Bahasa Inggris IKIP PGRI Pontianak, 2022)
The research was purposed to find out: (1) whether the use of the blog is effective in teaching writing skill; and (2) the significant level of using the blog in teaching writing skill. In term of investigating, the purposive sampling technique was used to select A-Morning class of the sixth-semester study of English Department of a private university in Pontianak to be the participant. The blog was used as a media to do drafting, revising and uploading the students’ writing texts. In both pre-test and post-test, the data gathered shows that the critical-value is higher than the t-value (20.224> 2.145), meaning that using a blog is significant in teaching the students’ writing skill. More, the significance level of the use of the blog is at a strong level since the value was higher than 1 (1.73) where most of the students could beneficially use the blog to improve their writing skills.